Analysis of Bisbenzylisoquinoline Alkaloids by Micellar Electrokinetic Chromatography with Large Volume Sample Stacking Technology - Zhu, Jinhua; Tian, Shufang; Zhou, Yanmei; Chen, Xingguo (Asian Journal of Chemistry, 2012)
This paper presents a sensitive method for separation and quantitative analysis of three structurally similar and hydrophobic bisbenzylisoquinoline alkaloids, liensinine, isoliensinine and neferine from embryo of the seed of Nelumbo nucifera Gaertn by micellar electrokinetic chromatography using a cationic surfactant, tetradecyltrimethyl ammonium bromide. In order to enhance the detection sensitivity of the analytes, large volume sample stacking technique is applied. Complete separation and stacking of the analytes is achieved within 15 min using 40 mM sodium dihydrogenphosphate (pH 6.40) containing 10 mM tetradecyltrimethyl ammonium bromide and 15 % (v/v) methanol as buffer. Detection limits in the range of 12.8-14.1 ng/mL for the analytes are obtained using large volume sample stacking. The sensitivity is improved 20-fold comparing with normal method. Finally, sample extraction is determined using this method and the result is in accordance with reference report.